Numerical simulation of the heating process of moving ingot - A. N. Chichko; A. S. Borozdin (Литьë и металлургия)
There is presented the model and computer calculations on numerical simulation of temperatures in the ingot, moving in the furnace, consisted of three thermal zones. There is received the distribution of the ingot temperatures for different speeds of its moving in the furnace.